Effect of hemodialysis and peritoneal dialysis on redox status in chronic renal failure patients: a comparative study - Mekki, Khedidja (BioMed Central, 2010)
OBJECTIVE: To investigate the effects of hemodialysis (HD) and periotoneal dialysis (PD) on oxidative stress in chronic renal failure patients (CRF). METHODS: 20 HD patients (M/F: 8/12, 36 ± 12 years) and 20 PD patients (M/F: 10/10, 40 ± 8 years) were compared with 20 end stage renal failure patients (CRF) (M/F: 4/16, 61 ± 13 years). RESULTS: Thiobarbituric acid reactive substances (TBARS) values were elevated in HD and decreased in PD compared to CRF (P < 0.05). TBARS-VLDL and TBARS-HDL(2 )were decreased in HD and PD, compared to CRF (p < 0.05). TBARS-LDL were higher in HD compared to CRF (p < 0.05). No significant difference in TBARS-HDL(3 )values between the three groups. Carbonyls were increased in HD (p < 0.05) and PD (p < 0.01) compared to CRF. Plasma superoxide dismutase activity (SOD) was decreased in HD compared to CRF and PD (P < 0.05). Glutathion peroxidase activity (GSH-Px) was decreased in HD and PD (P < 0.005), compared to CRF. Decrease in catalase activity was noted only in PD compared to CRF (P < 0.05). An increase in nitric oxide was noted in HD compared to CRF (p < 0.05). Albumin concentrations were higher in HD and PD compared to CRF (P < 0.001). Whereas uric acid concentrations were decreased in HD (P < 0.001) compared to CRF and PD. Bilirubin values were similar in all groups. Increased values of iron were noted in HD and PD, compared to PD (p < 0.001). CONCLUSION: HD and PD aggravate oxidative stress generated by uremia. HD accentuates lipid and protein peroxidation, while PD aggravates protein oxidation. However, the activity of antioxidant enzymes was altered by both dialysis treatments.